Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Berbantuan Media Flipchart Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik - Adelya Ayu Listiani Amran; Wurjinem Wurjinem; Sri Dadi (JURIDIKDAS, 2021)
This study aims to analyze the effect of the Numbered Head Together (NHT) type cooperative learning model assisted by flipchart media on student learning outcomes in thematic learning in class IV SD Negeri 24 Bengkulu City. This type of research is quantitative with a quasiexperimental method of the matching only pretest-posstest control group design. The research subjects were class IVB (experimental class) and IVA (control class). The research instrument of knowledge learning outcomes is written test sheets and differences in attitudes and skills learning outcomes ie observation sheets. The results showed that 1) the learning outcomes of knowledge namely the t-test obtained tcount for science subjects 2.22 and Indonesian subjects 2.44 with a table at a 5% significance level of 1.67 where tcount was greater than ttable, 2) the difference in attitudes learning outcomes with good and very good categories the average percentage in the experimental class was 77.75%, while the control class was 47.25% and 3) the differences in the learning outcomes of the skills with good and very good categories the average percentage in the experimental class at 82.50%, while the control class at 52.25%, meaning that there is an influence of the cooperative learning model Numbered Head Together (NHT) assisted by flipchart media. The conclusion of this study is that there is an influence of the Numbered Head Together (NHT) type of cooperative learning model assisted by flipchart media on student learning outcomes in thematic learning in class IV SD Negeri 24 Bengkulu City.